The effects of digitalization on the quality of marine economic development: evidence from a micro-level perspective - Weiteng Shen; Shunbin Zhong; Xinhua Yang (Frontiers in Marine Science, 2025)
Digitalization is transforming the marine economy at an accelerating pace, yet its effects on the Quality of Marine Economic Development (QMED) and the pathways driving these changes are underexplored. This study investigates these dynamics using an unbalanced panel of 168 A-share listed marine firms in China over the period 2003–2023. We apply a two-way fixed effects model to estimate the effect of digitalization on QMED and explore its mechanisms, complemented by heterogeneity analyses across firm sizes, industry types, government attention, and human capital levels. The results show that digitalization improves QMED, with a 0.01 rise in the digitalization index—about one-fifth of its mean—lifting Total Factor Productivity (TFP) of marine firms by roughly 0.599, or 6.85% of the average TFP. Digitalization boosts QMED by enhancing firms’ resource allocation efficiency and spurring technological innovation. Larger firms benefit more than smaller ones, while labor-intensive industries outpace capital-intensive ones in QMED gains. Higher human capital levels weaken digitalization’s positive effect on QMED. These findings suggest practical strategies for practitioners, such as adopting cost-effective digital tools like automation and big data analytics in labor-intensive sectors and providing subsidies or financing to support smaller firms’ digitalization. These insights highlight digitalization’s uneven effects and provide a foundation for targeted policy design to enhance marine economic development.